Autologous, lentivirus‐modified, T‐rapa cell “micropharmacies” for lysosomal storage disorders - Murtaza S Nagree; Tania C Felizardo; Mary L Faber; Jitka Rybova; C Anthony Rupar; S Ronan Foley; Maria Fuller; Daniel H Fowler; Jeffrey A Medin (EMBO Molecular Medicine)
Abstract T cells are the current choice for many cell therapy applications. They are relatively easy to access, expand in culture, and genetically modify. Rapamycin‐conditioning ex vivo reprograms T cells, increasing their memory properties and capacity for survival, while reducing inflammatory potential and the amount of preparative conditioning required for engraftment. Rapamycin‐conditioned T cells have been tested in patients and deemed to be safe to administer in numerous settings, with reduced occurrence of infusion‐related adverse events. We demonstrate that ex vivo lentivirus‐modified, rapamycin‐conditioned CD4+ T cells can also act as next‐generation cellular delivery vehicles—that is, “micropharmacies”—to disseminate corrective enzymes for multiple lysosomal storage disorders. We evaluated the therapeutic potential of this treatment platform for Fabry, Gaucher, Farber, and Pompe diseases in vitro and in vivo. For example, such micropharmacies expressing α‐galactosidase A for treatment of Fabry disease were transplanted in mice where they provided functional enzyme in key affected tissues such as kidney and heart, facilitating clearance of pathogenic substrate after a single administration.